The enterprise of science in Islam : new perspectives - Hogendijk, J. P.; Sabra, A. I. (Dibner Institute studies in the history of science and technology., 2003)
"Between A.D. 800 and 1450, the most important centers for the study of what we now call "the exact sciences"--Including the mathematical sciences of arithmetic, geometry, and trigonometry and their applications in such fields as astronomy, astrology, geography, cartography, and optics - were not in Europe but in the vast, multinational Islamic world." "This book offers an overview of this newly energized field of historical investigation. The topics discussed include cross-cultural transmission; transformations of Greek optics; the philosophy and practice of mathematics; numbers, geometry, and architecture; the transmission of astronomy; and science and medicine in the Maghrib. The emphasis throughout the book is on the transmission of scientific knowledge, either from one culture to another or within the medieval Islamic world."--Jacket